An assessment of LGUs' capability to implement a project of transforming marginal uplands into productive areas - Mendoza, M. E. T.; Visco, E. S.; Jimena, C. G. (2003)
This study aimed to assess the capability of LGUs (Brgy. Kapatalan and Brgy. Magsaysay) to implement a project component designed for income generation and poverty alleviation. Results revealed that the LGUs under study lacked competencies on project development, implementation, monitoring and evaluation. Inclusion of partner communities' assessment in terms of capabilities and social preparation in the initial phase of the project was recommended. Social preparation in the initial phase of the project was recommended. Social preparation should serve as a planning and decision making tool in the initial phase of project development and management. Community organizing or capacity building of local organization, where academe can be involved should be integral throughout the project cycle management to ensure the project acceptability and to safeguard the social benefits of the community.
Keywords: Local Government Units; Community development projects